2019
DOI: 10.30733/std.2019.01241
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Impression Cytology in Ocular Surface Diseases

Abstract: İmpresyon sitolojisi (IC) selüloz asetat filtre kağıtları kullanılarak, oküler yüzeyin çeşitli bozukluklarının tanısına yardımcı olan basit, noninvaziv bir tekniktir. Bu bozukluklar arasında oküler yüzey skuamöz neoplazisi, kuru göz sendromu, limbal kök hücre eksikliği, spesifik viral enfeksiyonlar, vitamin A eksikliği, alerjik bozukluklar, konjonktival melanozis ve malign melanom yer alır. IC, oküler yüzey hastalığının teşhisine yardımcı olmak, oküler yüzey hastalığının patofizyolojisini daha iyi anlamak ve k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…CIC is a useful technique which enables clinicians to evaluate the epithelial cell morphology, assess nuclear and cytoplasmic characteristics, and quantify the goblet cell density in the conjunctiva. [ 9 10 ] We found that there was more squamous metaplasia and goblet cell loss in the bulbar conjunctiva in Group 1 and Group 2 when compared with control subjects. Indeed, the CIC score was higher in Group 1 (severe KC) than in Group 2 (mild KC) but the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…CIC is a useful technique which enables clinicians to evaluate the epithelial cell morphology, assess nuclear and cytoplasmic characteristics, and quantify the goblet cell density in the conjunctiva. [ 9 10 ] We found that there was more squamous metaplasia and goblet cell loss in the bulbar conjunctiva in Group 1 and Group 2 when compared with control subjects. Indeed, the CIC score was higher in Group 1 (severe KC) than in Group 2 (mild KC) but the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 78%
“…Conjunctival impression cytology (CIC) is a diagnostic test for DED and squamous metaplasia in ocular surface disease. [ 9 10 ] CIC is a minimally invasive biopsy method of obtaining specimens from the conjunctiva and assessing the density of conjunctival goblet cells.…”
Section: Introductionmentioning
confidence: 99%
“…Impression cytology samples were collected using nitrocellulose acetate filter papers (Filter‐Lab, Filtros Anoia S.A., Barcelona, Spain) by applying light pressure for 10 s on the inferior temporal bulbar conjunctiva at a distance of 3 mm from the limbus. Specimens were fixed in a solution containing glacial acetic acid, 37% formaldehyde, and 70% ethanol with a 1:1:20‐volume ratio and stained with hematoxylin‐eosin and periodic acid‐Schiff stains 22 . The CIC specimens were evaluated and graded (Grade 0, 1, 2, or 3) with the Nelson grading system by a specialized pathologist (P.O.)…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were fixed in a solution containing glacial acetic acid, 37% formaldehyde, and 70% ethanol with a 1:1:20-volume ratio and stained with hematoxylin-eosin and periodic acid-Schiff stains. 22 The CIC specimens were evaluated and graded (Grade 0, 1, 2, or 3) with the Nelson grading system by a specialized pathologist (P.O.) who was blinded to the groupings and clinical information.…”
Section: Cic Samples and Histopathological Evaluationmentioning
confidence: 99%
“…These mucins, along with the water and electrolytes secreted by the lacrimal gland and the lipids produced by the Meibomian glands, form the tear lm. Alterations in the function of goblet cells lead to changes in tear composition that can result in different pathologies [7]. A histological classi cation of squamous metaplasia on the ocular surface is signi cant because doctors observe patients, classify and treat them based on their clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%